AI-Generated Affirmations and Self-Confidence among Filipino College Students - Irish Robin Quinaño; Anna Liza Bustamante; Stephanie Lopez; Kallie Ysavelle Segundo; Kimberly Ann Cantilero; Jerald Vergara; Antonio Ponciano Rodil (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The growing presence of artificial intelligence (AI) in everyday life has opened new possibilities for supporting psychological well-being, including the use of AI-generated affirmations to strengthen positive self-perceptions. This study investigated whether AI-generated affirmations could influence the self-confidence of Filipino college students. Using a quasi-experimental pretest-posttest control group design, the study involved 280 undergraduate students from a private university in the Philippines. Participants were assigned either to an experimental group that received AI-generated affirmations or to a control group that did not receive the intervention. Self-confidence was measured before and after the intervention using a standardized self-report scale. Data were analyzed through paired-samples and independent-samples t-tests to examine changes within and between groups. Findings showed a significant increase in self-confidence among students who received the AI-generated affirmations, whereas the control group showed no significant change. These results suggest that even brief, automated affirmations may help improve how students view themselves, particularly in relation to confidence. The findings also point to the potential of AI-based tools as accessible and scalable forms of support for student well-being in educational settings. More broadly, the study contributes to the growing discussion on how AI can be used not only for academic tasks, but also for psychological and emotional support among students.